Effect of money turnover rate on efficiency of national economy - Pshinko, O. M.; Myamlin, V. V.; Myamlin, S. V. (Science and Transport Progress, 2012)
Some provisions of an entirely new model of economic management having as its base “The Theory of High Efficient National Economy” are under consideration. The separate functions of money in the modern world are critically examined, and the contradictions among them are highlighted. It is demonstrated on how does the money turnover rate influences on the national economy efficiency. Ways to increase the rate of money turnover are shown. An absolutely new scheme of functioning the state monetary system is suggested.